2015
DOI: 10.1002/aqc.2564
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the population viability of a threatened amphibian with a fast life‐history

Abstract: 1.A bias in conservation research has meant that population viability analysis has focused primarily on mammals and birds with slow life histories. The global amphibian decline has demonstrated the capacity for fast life-history species to experience decline. However, little is known about the viability of remnant populations of these species as patterns of decline cannot be inferred from other species with different life-history strategies.2. Population viability analysis was performed on the threatened frog,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Other studies (e.g. Pickett, Stockwell, Clulow, & Mahony, ) have already revealed that egg–juvenile survival is fundamental for the conservation of amphibian populations. As further confirmation, in Podere la Querciola within the SCI Stagni della Piana Fiorentina e Pratese, the deliberate introduction of mosquitofish by local people caused the abandonment of two important breeding sites by T. carnifex , H. intermedia , and P .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies (e.g. Pickett, Stockwell, Clulow, & Mahony, ) have already revealed that egg–juvenile survival is fundamental for the conservation of amphibian populations. As further confirmation, in Podere la Querciola within the SCI Stagni della Piana Fiorentina e Pratese, the deliberate introduction of mosquitofish by local people caused the abandonment of two important breeding sites by T. carnifex , H. intermedia , and P .…”
Section: Discussionmentioning
confidence: 98%
“…In ecologically compromised water bodies with low availability of other prey and few hiding places (e.g. with regular clearing of aquatic vegetation), the presence of just a few, small amphibian larval groups and the introduction (or the absence of management) of mosquitofish populations could dramatically increase the risk of amphibian reproductive failure.Other studies (e.g Pickett, Stockwell, Clulow, & Mahony, 2016). have already revealed that egg-juvenile survival is fundamental for the con-servation of amphibian populations.…”
mentioning
confidence: 99%
“…model type and model structure) and the data used to inform the model (quality and quantity); these need to be transparently reported for a PVA's outcomes to contribute effectively to conservation plans (Morrison et al 2016). A global bias in conservation science research effort towards accessible and charismatic taxonomic groups with slow life-histories, predominantly birds and mammals, has been widely discussed (Clark & May 2002;Darwall et al 2011;Pickett et al 2016). It is often assumed that findings from better studied taxa will act as surrogates for phylogenetically related lesser studied groups (Grenyer et al 2006;Rodrigues & Brooks 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, PVA requires detailed species knowledge, which can be challenging for rare and data‐poor species. One approach to dealing with uncertainty is sensitivity analysis, which can explicitly address sources of uncertainty and their influence on potential outcomes (Naujokaitis‐Lewis, Curtis, Arcese, & Rosenfeld, ; Pe'er et al, ; Pickett, Stockwell, Clulow, & Mahony, ), highlight vulnerabilities, and direct future research needs (Curtis & Naujokaitis‐Lewis, ; Curtis & Vincent, ). It can also be used to identify important trade‐offs within a system (Johst et al , ) that can inform management options, including biodiversity offsets.…”
Section: Introductionmentioning
confidence: 99%